The Effects of Transcutaneous Electrical Nerve Stimulation on Postural Control in Patients with Chronic Low Back Pain - Rojhani Shirazi, Zahra; Rezaeian, Tahere (Journal of Clinical Physiotherapy Research, 2017)
Introduction: To study the effects of transcutaneous electrical nerve stimulation (TENS) on postural control in chronic low back pain (CLBP) patients. Materials and Methods: The current study is an experimental one with twenty eight patients suffering from chronic LBP (25-45 Y/O). At first non-random sampling technique was used to have the study subjects selected, using block randomization, then, we assigned them to main groups known as intervention and control. The mean center of pressure (COP) velocity and displacement were measured at three time intervals; prior to the intervention, once the intervention was provided and thirty minutes after it. The tests were done with eyes open and closed on a force platform. Sensory electrical stimulation was applied through the TENS device. Descriptive statistics, independent sample test, repeated measurement and ANOVA with repeated measurement on time were used for data analysis. Results: The results of the present study demonstrated that the application of sensory electrical stimulation among patients with CLBP could improve the postural control in Medio-lateral immediately after and 30 minutes following the application of TENS among the patients with their eyes closed (P<0.05). Also, COP displacement and velocity in ML direction with eyes closed significantly decreased immediately and 30 min after application of sensory electrical stimulation in the intervention group in comparison with the control group (P<0.05). Conclusion: Low frequency TENS with contraction level amplitude seems to have positive effects on postural control in patients suffering from CLBP. So, this study showed the effectiveness of low frequency TENS to imprive postural control in patients with CLBP. Key words: Chronic Low Back Pain, Postural Control, Transcutaneus Electrical Nerve Stimulation